2019
DOI: 10.1111/josi.12310
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberal Ideology and the Justification of Inequality in Capitalist Societies: Why Social and Economic Dimensions of Ideology Are Intertwined

Abstract: In this article we analyze data from high-quality surveys conducted in the United States and the United Kingdom that included multiple symbolic and operational measures of political ideology and psychological orientations. Our overarching goal is to elucidate the nature of conceptual and empirical connections between neoliberalism and social conservatism. In so doing, we revisit three major questions about public opinion in neoliberal societies: (1) Are ordinary citizens "innocent" of ideology? (2) Are social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
132
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(160 citation statements)
references
References 86 publications
6
132
0
5
Order By: Relevance
“…Indeed, Bettache and Chiu (; ) showed that their video measure consistently correlated positively with the endorsement of cohesiveness‐enhancing social norms (e.g., a strict morality or authoritarianism) and conservatism. Moreover, this finding supports Azevedo et al.’s () argument, that economic and social dimensions of ideology are not independent. Individuals who adhere to social conservatism (e.g., tight norms and traditionalism) are likely to embrace neoliberal economics.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Indeed, Bettache and Chiu (; ) showed that their video measure consistently correlated positively with the endorsement of cohesiveness‐enhancing social norms (e.g., a strict morality or authoritarianism) and conservatism. Moreover, this finding supports Azevedo et al.’s () argument, that economic and social dimensions of ideology are not independent. Individuals who adhere to social conservatism (e.g., tight norms and traditionalism) are likely to embrace neoliberal economics.…”
Section: Resultssupporting
confidence: 87%
“…To replicate, extend, and compare the results of Bay‐Cheng et al.’s () research in two Asian contexts, Hong Kong and India, we also used Rotter's () Internal–External (I–E) Control Scale and Ho et al.’s () seven‐question Social Dominance Orientation (SDO) Scale. SDO measures the belief that social hierarchies are natural and justified, which is in line with the neoliberal idea of competition in the free marketplace where success and failure are deemed personal responsibilities and thus the best deserve to be on top and those who fail deserve to be left behind (e.g., Azevedo et al., ; Perez & Salter, ). Hence, we expect SDO to positively relate to neoliberal beliefs across all three cultural contexts (Hypothesis 1a).…”
Section: Overview Of Present Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…A large body of social science research lends insight into the attitudes and beliefs that legitimize harsh work requirements and neoliberal welfare reform, more generally (Azevedo, Jost, Rothmund, & Sterling, ; Bullock & Reppond, ; Rodríguez‐Bailón et al., ). In the United States, a country distinguished by its adherence to rugged individualism and capitalism, welfare recipients are stereotyped as dependent “freeloaders” who violate dominant values by choosing welfare over work (Henry, Reyna, & Weiner, ).…”
Section: Deconstructing the Ideological Appeal Of Neoliberal Work Reqmentioning
confidence: 99%
“…In the United States, a country distinguished by its adherence to rugged individualism and capitalism, welfare recipients are stereotyped as dependent “freeloaders” who violate dominant values by choosing welfare over work (Henry, Reyna, & Weiner, ). Azevedo and his colleagues () found that endorsement of pro‐capitalist, neoliberal economic attitudes is associated with “general, economic, and gender‐specific forms of system justification” (p. 80). Individualism (i.e., beliefs emphasizing individual responsibility and freedom), meritocratic beliefs (i.e., anyone, regardless of their class background or family of origin, can rise up the socioeconomic ladder through hard work and perseverance), and the Protestant work ethic (i.e., the belief that hard work, deferment of immediate rewards, and frugality will be rewarded with material success), in particular, make neoliberal practices appear “natural” and as a result, they go largely “unchallenged as the default logic for making public policy” (Schram, , p. 311).…”
Section: Deconstructing the Ideological Appeal Of Neoliberal Work Reqmentioning
confidence: 99%